The Efficacy of Garlic in Alleviating Phenanthrene and Chrysene Induced Pulmonary Injury in Rats - Md. Saad, Wan Mazlina (2003)
Air pollution specifically referring to haze consists of numerous particles including polycyclic aromatic hydrocarbons (PAH). These particles consist of various compound including phenanthrene (Phen) and chrysene (Chry). Both of these are among hazardous compounds which are found during the haze periods back in 1997 in Malaysia. This situation had a great impact on health and also on the economic status of the country as well. In finding strategies and bringing about a remission of noxious haze effects in humans, acute and chronic exposure to Phen, Chry and their combination were studied in rats. The acute exposure studies were conducted to evaluate apoptosis in the lung of rats following with Phen, Chry and Phen+Chry. Rats not receiving any treatment served as control while those administered with Phen, Chry and Phen+Chry were instilled at the dose of 14.87ng (7.4mI), 7.07ng (3.5ml) and 21.94ng (10.9m1) respectively. Animals in control and treated group were euthanised at 1, 8 and 24 hours post instillation (p.i.). Apoptosis detection was made on H&E stained paraffin-embedded sections, terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling analysis (TUNEL) and DNA laddering of lung samples. Selected proteases were also examined from lung lavage of all rats. Apoptosis were observed in pneumocytes and bronchial epithelium of rats euthanised at the specific time pj and the percentage of apoptotic cells increased with time, especially in 24 hours pj.which were highest for group especially the combination group (p<0.05). This was confirmed by TUNEL analysis and DNA laddering. As for proteases, there was also elevation in the content of total protein, number of neutrophil and level of elastase. This activity also showed increased with time as compared to normal. The chronic exposure study was conducted on changes in the lung of Phen, Chry and Phen+Chry. These rats were kept for three months to assess histopathologic findings, immune response, level of marker enzyme, proteases and the effects of raw garlic as an anti-tumour factor. Rats from the control group, Phen, Chry and Phen+Chry were daily fed with commercial rat pellet while rats from garlic (G), Phen+G, Chry+G and Phen+Chry+G were fed with rat pellet mixed with garlic at the rate of 80 mg/kg body-weightlrat/day. From the observation rats from Phen, Chry and Phen+Chry group showed growth disturbances in pneumocytes and bronchial epitheliam including pulmonary mechanisms. Morphological changes including hyperplasia and metaplasia were among the finding in treatment groups. Necrosis was also detected in these groups. Rats induced with Phen and Chry particles showed a low level of IgG and IgA and alveolar macrophage activity in the lung. Furthermore, rats treated with these particles showed an elevation in glutathione-S-transferase and proteases activity. Rats treated with garlic had no significant lesions and marked elevation in pulmonary defense mechanism. Lastly, acute and chronic exposure to environmental pollutants such as Phen and Chry incites injury to the lung. Garlic has shown to be a great potential in alleviating chronic injury induced by Phen and Chry in the treated rats.